Balancing Work, Training Apprentices and Learning at Workplaces: Experiences of TVET Graduates of Motor Vehicle Mechanics - Garuzooka, Francis John; Nuwagaba, Ephraim Lemmy; Mudondo, Constance; Ngaka, Willy (East African Nature and Science Organization, 2024)
This study investigated the activities that graduates of motor vehicle mechanics engaged in while working in garages and how these activities are balanced. In-depth face-to-face interviews were conducted with twelve graduates to collect qualitative data. Data was thematically analyzed and framed within the Communities of Practice theoretical framework. Findings suggest that although TVET institutions do not prepare their learners to balance work, learning, and training, graduates can perform these tasks using the knowledge acquired from their workplaces. Graduates who have a considerable level of formal education can devise strategies for balancing different responsibilities than those with low levels of formal education. However, challenges such as injuries, unprofessional conduct of garage managers, illiteracy, language barriers, and indiscipline amongst trainees constrain the balancing of these tasks. We recommend that TVET institutions train their learners to be multitasking to enhance their capacity to perform multiple tasks at workplaces. Additionally, employers need to avail time and other resources to enable graduates to learn new skills at the workplace so that they can handle multiple tasks such as repairing vehicles, training, and learning